Juvenile Delinquency in Novel Clockwork Orange By Anthony Burgess - Bena Yusuf Pelawi (Bina Nusantara University, 2014)
The study aimed to reveal the role of literary work, especially a novel in reflecting the social fenomena, the juvenile delinquency in the twentieth century. The data source was an English novel ‘Clockwork Orange’ written by Anthony Burgess. The research applied library research by using reflection theory introduced by Georg Lukacs. Analysis was presented in three parts, those were the identification of major character, social setting, and the reflection of juvenile delinquency.The findings were as follows. First, the major character was Alex as his hig intensity in all the events that build the whole story. Second, the social setting described the life of teenagers, especially the juvenile delinquency as social fenomena in society. Third, the role of literary work in revealing the problem above faced by the twentieth century society. Finally, it can be concluded that the literary work has played a very important role in revealing the social fenomena.